Result on Variational Inequality Problem - Nashine, Hemant Kumar (Sarajevo Journal of Mathematics, 2024)
The aim of this paper is to present an improved and extended version of the variational inequality problem of Vetrivel and Nanda [7] by using a weaker condition in the topological vector space and without using the result of Lassonde [3]. 1991 Mathematics Subject Classification. 90C30, 49N15